Warm white-light emitting silica films prepared using lead-free double perovskite QDs. Issue 28 (29th June 2021) - Li, Zexin; Sun, Fenglei; Song, Haining; Zhou, Haifeng; zhou, Yifei; Yuan, Zhenlei; Guo, Peng; Zhou, Guangjun; Zhuang, Qianqian; Yu, Xiaoqiang
Abstract : Bi-doped Cs2 Ag x Na1− x InCl6 quantum dots with a wide luminescence domain were prepared by a heat injection method, and warm white light emitting films with good photostability and thermal stability were prepared by SiO2 coating. Abstract : Lead-free double perovskite has attracted widespread attention due to its good stability and non-toxicity. In this work, Cs2 Ag x Na1− x InCl6 quantum dots were synthesized via a thermal injection method using non-toxic precursors. Based on the wide spectrum of self-bound excitons, the quantum dots achieved white light emission. Bi-doped Cs2 Ag x Na1− x InCl6 quantum dots with excellent luminescence performance have the same cubic structure, and they have a larger Stokes shift. The cubic perovskite space group is Fm 3̄ m, and [NaCl6 ], [AgCl6 ] and [InCl6 ] octahedrons alternately appear in the cubic structure. The photoluminescence quantum yield of Cs2 Ag x Na1− x InCl6 is improved by doping with a small amount of Bi; the PL QY increased to 57.3% with an obvious emission peak at 600 nm. The stability and luminescence intensity of perovskite QDs were further enhanced by SiO2 coating and a Cs2 Ag x Na1− x InCl6 :Bi-SiO2 thin film was prepared using perhydropolysilazane as the precursor. The materials have huge application potential in the field of white light emission and display.